Strategi Pengembangan Pantai Melasti sebagai Daya Tarik Wisata di Desa Ungasan, Kecamatan Kuta Selatan, Kabupaten Badung - Julyantara, I Putu Widhi Eka; Sunarta, I Nyoman (JURNAL DESTINASI PARIWISATA, 2019)
Melasti beach is a tourist attraction of the beach that is just starting to develop. Melasti Beach still in development in the governance by the village of Ungasan and yet the existence of a management system. Melasti beach is located in Ungasan, South Kuta, Badung Regency, has the potentialities are wonderful and interesting to develop. The assumption behind this is based on the chosen research topic "melasti Beach Development Strategy as a tourist attraction in the village of Ungasan, South Kuta, Badung Regency. Data types and data sources that are used i.e. qualitative data, primary and secondary data. Data collection done by way of observation, unstructured interviews, study kepustakan, documentation, research instrument is the guidance interview. The analysis of the data used is descriptive qualitative data analysis with the use of tourism potential and analysis approach to SWOT analysis which clearly sets forth the findings based on the issues examined with accurate data sources. In the results of this research demonstrating that the Melasti Beach has the potential of nature is very beautiful, it also has the potential of culture as well as potential human or artificial to developed, capable of attracting tourists visit. Although still in the development phase is already visited by tourists and foreigners to the archipelago. The conclusions from the results of Shore Development Melasti is need for management systems, many still lack facilities to complement the tourist attraction due to the lack of funds and contributions from the Government is still waiting for him. Keywords: Tourist Attraction, Tourism Potential, Strategy Development